Relatedness and synergies of kind and scale in the evolution of helping - Jorge Pe\~na; Georg Nöldeke; Laurent Lehmann (University of Basel, Center of Business and Economics (WWZ), 2014)
Relatedness and synergy affect the selection pressure on cooperation and altruism. Although early work investigated the effect of these factors independently of each other, recent efforts have been aimed at exploring their interplay. Here, we contribute to this ongoing synthesis in two distinct but complementary ways. First, we integrate models of n-player matrix games into the direct fitness approach of inclusive fitness theory, hence providing a framework to consider synergistic social interactions between relatives in family and spatially structured populations. Second, we illustrate the usefulness of this framework by delineating three distinct types of helping traits (“whole-group”, “nonexpresser-only” and “expresser-only”), which are characterized by different synergies of kind (arising from differential fitness effects on individuals expressing or not expressing helping) and can be subjected to different synergies of scale (arising from economies or diseconomies of scale). We find that relatedness and synergies of kind and scale can interact to generate nontrivial evolutionary dynamics, such as cases of bistable coexistence featuring both a stable equilibrium with a positive level of helping and an unstable helping threshold. This broadens the qualitative effects of relatedness (or spatial structure) on the evolution of helping.
Keywords: 330; evolution of helping; relatedness; synergy; inclusive fitness; evolutionary games